Positive electrode material and preparation method and application thereof
By using a positive electrode material with bimodal particle size distribution in the lithium-rich manganese-based positive electrode, the problem of low compaction density of the lithium-rich positive electrode is solved, and a higher volume energy density and better Excellent cycle stability.
Patent Information
- Application Number
- CN202510018772.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
AI Technical Summary
The compaction density of lithium-rich manganese-based positive electrode is low, resulting in its volumetric energy density not high enough to meet the power battery's demand for higher energy density and longer range.
A positive electrode material with bimodal distribution of particle size is used to improve the compaction density and cycle stability of the material by forming primary spherical particles of different sizes that form large and small secondary spherical particles. Specific methods include synthesizing hydroxide precursors of small- and large-size secondary spherical particles and forming a bimodal particle size distribution through sintering and crushing treatment.
It significantly improves the compaction density and cyclic stability of the positive electrode material, enhances the volume energy density, and meets the demand for high-performance positive electrode materials of the power battery.
Smart Images

Figure CN119447287A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion secondary batteries have become the best choice for mainstream electric vehicle power batteries. The main performance of lithium-ion secondary batteries is largely determined by the positive electrode material. One of the most important performances is energy density, which determines one of the most critical parameters of electric vehicles: driving range. At present, the mainstream positive electrode materials for power batteries show a two-strong pattern: lithium iron phosphate materials and medium-high nickel ternary materials. These two types of positive electrode materials have distinct characteristics. Among them, lithium iron phosphate positive electrodes have excellent safety and cycle stability, but low energy density. Medium-high nickel ternary materials have high energy density, good cycle stability, and safety performance is inferior to lithium iron phosphate. Therefore, manganese-based positive electrode materials with more balanced comprehensive performance are the next generation of positive electrode solutions that the industry is constantly pursuing. Among them, lithium-rich manganese-based positive electrodes are typical representatives. They have high energy density, safety performance, cycle stability, and lower cost than ternary positive electrodes. However, there are still some problems in the industrialization of lithium-rich positive electrodes at this stage, such as the problem of low compaction density.
[0003] At present, the industrialized voltage of lithium-rich manganese-based batteries is 4.5V vs Graphite and below. Within this voltage range, its specific capacity can reach 230mAhg -1 , the higher nickel cathode still has advantages, higher than the medium nickel high voltage ternary cathode specific capacity, corresponding to the specific capacity range of lithium-rich manganese-based average discharge voltage is 3.6~3.65V vs Graphite, slightly lower than the medium and high nickel ternary cathode by 0.05~0.1V. Combined with the above, the specific mass energy density of the lithium-rich cathode is basically the same as that of the ultra-high nickel ternary cathode.
[0004] In fact, in addition to considering the energy density of the power battery in terms of mass energy density, the energy density of the power battery must also be considered in terms of volume energy density, because sedans and SUVs are the mainstream among passenger cars, and the volume energy density determines the size of the battery pack energy that can be installed in the same level of models. Higher volume energy density allows passenger cars to carry higher energy battery packs, improve driving range, and make the interior space wider and more comfortable to ride. The lithium-rich manganese-based positive electrode has a higher proportion of Li atoms in the unit cell, and the relative atomic mass of manganese is slightly lower than that of nickel and cobalt, resulting in a lower true density of the lithium-rich manganese-based positive electrode unit cell than that of medium- and high-nickel ternary materials. Generally speaking, the true density of the lithium-rich manganese-based positive electrode unit cell is between 4.3 and 4.4 g / cm 3 , and the true density of the high nickel cathode unit cell is 4.8 g / cm 3 The compaction density of common high-nickel cathode powder is relatively high, reaching 3.5g / cm 3, while the available compaction density of lithium-rich cathode powder is currently only 2.8~2.9g / cm 3 Therefore, it is necessary to further improve the compaction density of the lithium-rich cathode so that its volume energy density is close to that of the ultra-high nickel ternary.
[0005] Since the kinetic performance of lithium-rich cathode is inferior to that of ternary cathode, the former's industrialized products are mostly in the form of secondary sphere aggregates, and single crystal and quasi-single crystal products are rarely used due to their low capacity. For secondary spherical products, the usual means to improve their compaction density is to develop products with dual particle size distribution. In ternary cathodes, due to the excellent kinetic performance of the material, the porosity and primary particle size of the large and small secondary spheres contained in the dual distribution or wide distribution products are usually close and relatively dense, which significantly improves the compaction density of the system and at the same time has excellent capacity. In lithium-rich cathode systems, due to the poor kinetic performance of lithium-rich materials, it is necessary to carry out targeted design of the primary particle size, porosity, and modification scheme of large and small particles of the dual distribution or wide distribution system, so that the system can take into account high capacity, high compaction density, and high stability. Summary of the invention
[0006] Based on the above, the present invention proposes a positive electrode material with a bimodal particle size distribution, in which the large and small secondary spherical particles that constitute it have primary spherical particle sizes of different sizes. Compared with the single-distribution lithium-rich positive electrode product, this system has higher compaction density, excellent cycle stability and capacity performance, can meet the performance requirements of power batteries for lithium-rich positive electrode products, and help accelerate the industrialization progress of lithium-rich positive electrodes.
[0007] The present invention provides a positive electrode material, wherein the particle size distribution curve of the positive electrode material is a bimodal distribution, the positive electrode material is composed of large-diameter secondary spherical particles and small-diameter secondary spherical particles, the large-diameter secondary spherical particles are composed of small-diameter primary spherical particles, the small-diameter secondary spherical particles are composed of large-diameter primary spherical particles, the large-diameter secondary spherical particles have a D50 of 8.0-12.0 μm, and the small-diameter secondary spherical particles have a D50 of 2.0-4.0 μm, wherein the maximum diameter of the small-diameter secondary spherical particles is no more than 5 μm, and the minimum diameter of the large-diameter secondary spherical particles is not less than 5 μm; and the average particle size of the small-diameter primary spherical particles and the large-diameter primary spherical particles meets the following requirements: 0.5≤l / m≤0.75, Wherein l is the average particle size of the small-diameter primary spherical particles, and m is the average particle size of the large-diameter primary spherical particles.
[0008] Compared with the prior art, the present invention proposes to use a positive electrode material with two secondary spherical particles having different primary spherical particle sizes to improve the compaction density and cycle stability of the positive electrode material. Among them, the secondary spherical particles with small particle size are composed of primary spherical particles with larger particle size, and the secondary spherical particles with large size are composed of primary spherical particles with smaller particle size. First of all, the capacity of the two secondary spherical particles with different particle sizes in the secondary spherical particles with mixed particle size with bimodal distribution is guaranteed to the greatest extent, and finally the mixed system has excellent capacity performance. The lithium-rich positive electrode kinetics are inferior to the ternary positive electrode. Therefore, in the secondary spherical particles with larger particle size, its capacity is more significantly affected by the size and stacking density of the primary spherical particles, and the capacity fluctuation is also more obvious.
[0009] Secondly, the compaction density of the volume is guaranteed to the greatest extent. The size of the primary spherical particles that make up the small-sized secondary spherical particles is appropriately increased to improve the packing density and structural strength of the small-sized secondary spherical particles, so as to avoid them from breaking during the pressing of the electrode and exposing the fresh interface, which affects the stability of the system. At the same time, the average size of the primary spherical particles is controlled not to exceed twice the average size of the primary spherical particles that make up the large-sized secondary spherical particles, so as to ensure the excellent capacity of the small-sized secondary spherical particles and balance the capacity and cycle stability of the dual-distribution system.
[0010] Appropriately increasing the size of the primary spherical particles that make up the small-size secondary spherical particles can also reduce their specific surface area. In the medium-to-high voltage (4.5V vs graphite) system, the interfacial side reaction is highly correlated with the specific surface area of the material. Reducing the specific surface area of the material has a good inhibitory effect on the interfacial side reaction, thereby improving the long-term stability of the system. Avoid various problems caused by interfacial side reactions, such as transition metal dissolution, electrolyte oxidation and decomposition, battery diving, and gas expansion.
[0011] This lithium-rich positive electrode system with a double distribution of secondary spherical particles with different primary spherical particle sizes has better pressure resistance than a single-size secondary spherical particle-type lithium-rich positive electrode, because its small-size secondary spherical particles are composed of large-size primary spherical particles, and its own structural strength is improved. Large-size secondary spherical particles are easy to break due to low structural strength if used alone due to their small primary spherical particle size, affecting long-term cycle stability. In the lithium-rich positive electrode with a double distribution of secondary spherical particle sizes described in the present invention, small-size high-strength secondary spherical particles will enter the gaps formed by large-size secondary spherical particles. Due to the high structural strength of small-size secondary spherical particles, they provide a stable support effect, improve the pressure resistance of the material, and then use a higher pressure to make the pole piece, obtain a higher compaction density, and effectively improve the volume energy density of the lithium-ion battery.
[0012] In one possible embodiment, the chemical formula of the positive electrode material is Li 1+x Nit Mn u M 1-x-t-u O 2-z S z , wherein 0.1≤x≤0.2, 0.1≤t≤0.4, 0.5≤u≤0.7, 0.002≤z≤0.02, 0.95≤x+t+u<1.0, and M is selected from one or more of Nb, Cr, Ta, P, Mg, Ti, Mo, W, Sn, Sr, Al, Y, La, Zr, Ce, Si, Ba, and B.
[0013] Compared with the prior art, the present invention can significantly improve the theoretical capacity of the material by adjusting the parameters such as x, t, u, z in the formula and selecting the appropriate M element, thereby improving the energy density of the battery. At the same time, by doping different types of M elements and controlling their content ratio, the change of the crystal structure during the charge and discharge process can be effectively suppressed, thereby improving the cycle performance and service life of the material.
[0014] In a possible embodiment, a coating layer is further included, and the material of the coating layer is selected from one or more of Al2O3, LiAlO2, Li3PO4, and AlPO4, and the mass proportion of the coating layer in the positive electrode material is 0.2-2.0wt%.
[0015] Compared with the prior art, the present invention further provides a coating layer, which can effectively inhibit direct contact between the electrolyte and the positive electrode material and reduce the occurrence of side reactions, which helps to prevent damage to the material structure and thus extend the service life of the battery. Appropriate coating treatment can reduce the negative impact of material volume changes during charging and discharging, maintain good particle integrity, and thereby alleviate the problem of capacity decreasing over time. The coating layer can also improve the interface properties between the positive electrode and the electrolyte, promote lithium ion transmission while preventing electrons from passing through, thereby improving the overall efficiency of the battery.
[0016] In a possible implementation, the D50 of the positive electrode material is 5.0-8.0 μm.
[0017] In a possible embodiment, the average grain size of the positive electrode material is 80-130nm. It is worth mentioning that the present invention uses the Rietveld method to refine the XRD spectrum of the positive electrode material of the present invention. In the XRD refinement result, the average grain of the positive electrode material is 80-130nm. This size is the best average grain size range suitable for medium and high voltage lithium-rich positive electrode materials. Within this range, the material capacity can be fully utilized, and the lattice stress will not increase significantly due to excessive grain size. At the same time, the average grain size of not less than 80nm ensures that the primary particle size of the material will not be too small, and there will be no serious side reactions caused by the infiltration of electrolyte due to too many grain boundaries, and the structural strength is relatively high.
[0018] In a possible embodiment, the Span value of the positive electrode material is 1.2-1.6, where Span=(D 90 -D 10 ) / D 50 .
[0019] In one possible embodiment, the specific surface area of the positive electrode material is 0.7-3.0 m 2 / g.
[0020] In one possible embodiment, the cathode material has a powder compaction density of ≥3.05 g / cm2 at a pressure of 3.5 T. 3 .
[0021] In a possible embodiment, in the particle size distribution curve of the positive electrode material, the relative height of the left peak and the relative height of the right peak satisfy: 0.3≤I A :I B ≤0.6, where I A is the relative height of the left peak, I B is the relative height of the right peak.
[0022] Compared with the prior art, the large-size secondary spherical particles and the small-size secondary spherical particles described in the present invention have a bimodal distribution of lithium-rich positive electrode system, and the left peak intensity is limited to 0.3~0.6 times the right peak intensity. Within this range, the system compaction density is significantly higher than that of a single particle size distribution product.
[0023] In a possible embodiment, the cross-sectional porosity of the large-size secondary spherical particles and the cross-sectional porosity of the small-size secondary spherical particles satisfy: 1.2≤α / β≤1.8, wherein α is the cross-sectional porosity of the large-size secondary spherical particles, and β is the cross-sectional porosity of the small-size secondary spherical particles.
[0024] Compared with the prior art, the present invention further limits the porosity of the secondary sphere cross section to ensure that the large-diameter secondary sphere particles have a moderately higher porosity than the small-diameter secondary sphere particles. The functions are: 1. Enhance the ion transmission efficiency: within this ratio range, large-diameter particles provide larger channels, which are conducive to electrolyte penetration and rapid ion transmission; while small-diameter particles increase the total surface area and provide more active sites. This combination can significantly improve the ion conductivity of electrode materials; 2. Increase the reaction interface: small-diameter particles can provide more reaction interfaces due to their higher specific surface area, promoting the occurrence of chemical reactions. At the same time, the presence of large-diameter particles ensures the structural stability of the material, avoids structural collapse or agglomeration caused by excessive refinement, and thus improves the utilization rate of the overall active material.
[0025] The second object of the present invention is to provide a method for preparing a positive electrode material, the preparation method specifically comprising the following steps: S1. synthesizing a hydroxide precursor of small-size secondary spherical particles and a hydroxide precursor of large-size secondary spherical particles respectively; S2, mixing the lithium source, additives, the hydroxide precursor of the small-size secondary spherical particles and the hydroxide precursor of the large-size secondary spherical particles obtained in step S1, sintering them once, cooling them, and then crushing and sieving them to obtain the positive electrode material.
[0026] Since the positive electrode material has a bimodal particle size distribution (large-size secondary spherical particles 8.0-12.0 μm and small-size secondary spherical particles 2.0-4.0 μm), the preparation method of the present invention adopts a method of separately synthesizing a hydroxide precursor of small-size secondary spherical particles and a hydroxide precursor of large-size secondary spherical particles, and independently optimizes the two precursors of different sizes, ensuring that the desired bimodal particle size distribution can be formed in the subsequent sintering process.
[0027] In a possible implementation, in step S1, the specific steps of synthesizing the hydroxide precursor of small-size secondary spherical particles are as follows: A1. Set the stirring speed to 600-1000 rpm and the temperature to 50-60°C. After passing the protective gas for exhaust treatment for 2-3 hours, add the metal salt solution, precipitant and complexing agent to maintain the pH of the reaction system at 9.5-11.0; A2, wait until the particle size grows to D 50 In the range of 2.0-4.0 μm, stop feeding and collect the slurry; A3, the slurry collected in step A2 is aged, washed, centrifuged, and dried in sequence to obtain a hydroxide precursor of small-size secondary spherical particles; The specific steps for synthesizing the hydroxide precursor of large-size secondary spherical particles are as follows: B1. Set the stirring speed to 600-1000 rpm and the temperature to 50-60°C. After introducing protective gas for exhaust treatment for 2-3 hours, add metal salt solution, precipitant and complexing agent to maintain the pH of the reaction system at 9.5-11.0; B2, wait until the particle size grows to D 50 In the range of 8.0-12.0 μm, stop feeding and collect the slurry; B3. The slurry collected in step B2 is subjected to aging, washing, centrifugation and drying treatments in sequence to obtain a hydroxide precursor of large-size secondary spherical particles.
[0028] It is worth mentioning that, unlike the steps of preparing the precursor required for small-sized secondary spherical particles, the present invention achieves the effect of regulating the primary particle size of the large-sized secondary spherical particle precursor by introducing an appropriate amount of oxygen when preparing the precursor required for large-sized secondary spherical particles, thereby controlling the primary particle size of the large-sized secondary spherical particles.
[0029] In some embodiments, in step A1 and step B1, the total molar concentration of the metal salt solution is 2-3 mol / L, and the solutes are nickel sulfate and manganese sulfate, wherein the molar ratio of nickel to manganese is the same as the ratio of the small-size secondary spherical particles, the precipitant is a sodium hydroxide solution with a concentration of 8-12 mol / L, and the complexing agent is an 8-12 wt% ammonia solution.
[0030] In some embodiments, the protective gas in step A1 is nitrogen, and the protective gas in step B1 is nitrogen containing 0.5-5.0 vol% oxygen.
[0031] In a possible implementation, the step S3 is also included, mixing the positive electrode material and the coating agent evenly, performing secondary sintering, cooling, crushing and screening in sequence to obtain a positive electrode material containing a coating layer, wherein the coating agent is selected from one or more of Al2O3, LiAlO2, Li3PO4, and AlPO4.
[0032] In a possible implementation manner, the parameters of the primary sintering are as follows: a heating rate of 1-3° C. / min, a sintering temperature of 900-950° C., and a holding time of 8-15 h.
[0033] In a possible implementation manner, the parameters of the secondary sintering are as follows: a heating rate of 1-3° C. / min, a sintering temperature of 500-700° C., and a holding time of 8-12 h.
[0034] Compared with the prior art, by setting the primary sintering parameters to a heating rate of 1-3°C / min, a sintering temperature of 900-950°C and a holding time of 8-15 hours, and the secondary sintering parameters to a heating rate of 1-3°C / min, a sintering temperature of 500-700°C and a holding time of 8-12 hours, the present invention ensures uniform heating, sufficient crystal phase transformation and structural optimization of the positive electrode material, thereby improving the structural stability, purity and electrochemical properties of the material, while reducing internal stress and defects, and ultimately achieving the preparation of high-quality, high-performance positive electrode materials.
[0035] The third object of the present invention is to provide an application of a positive electrode material in a lithium ion battery.
[0036] In summary, the dual-distributed positive electrode material described in the present invention has excellent capacity performance, high compaction density, and excellent cycle stability, and is a new type of high-performance positive electrode material suitable for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM image of the positive electrode material described in Example 1; Figure 2 It is a particle size distribution curve diagram of the positive electrode materials described in Example 1, Comparative Example 1 and Comparative Example 2; Figure 3 The figures are the powder compaction density diagrams of the positive electrode materials described in Example 1, Comparative Example 1 and Comparative Example 2 measured at different pressures; Figure 4 The cycle performance curves of the liquid button half-cells assembled with the positive electrode materials described in Example 1, Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0041] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0042] It is worth mentioning that in the detection method adopted in the embodiment of the present invention: Primary particle size, material specific surface area, and particle size determination: The morphology of the positive electrode materials obtained in all embodiments and comparative examples was observed by SEM, and the average thickness and length of at least 100 random primary particles in a selected area in the SEM were determined by Nano measure software; the specific surface area was determined by nitrogen adsorption BET method, and the determination was carried out with reference to the test method specified in national standard GB / T 19587-2017; the particle size was determined by laser particle size instrument, D 10 Indicates the particle size distribution based on volume, the particle size of the positive electrode material particles from the small particle size side when the cumulative volume reaches 10%; D 50 Indicates the particle size distribution based on volume, the particle size of the positive electrode material particles from the small particle size side when the volume cumulatively reaches 50%; D 90 Indicates the particle size distribution based on volume, the particle size of the positive electrode material particles from the small particle size side when the volume cumulatively reaches 90%; Determination of cross-sectional porosity: The positive electrode materials obtained in all embodiments and comparative examples were photographed using SEM, and then the grayscale of a single secondary sphere cross section of the material was quantitatively analyzed using ImageJ software. Specifically, the RGB threshold was first set to 90, and the area ratio of the region in the RGB range of 0 to 90 in the selected region image of the single secondary sphere cross section was obtained, recorded as X1; similarly, the area ratio of the region in the RGB range of 0 to 252 in the same selected region image of the same single secondary sphere cross section was recorded as X2, and the material cross-sectional porosity was obtained as X1 / X2*100%. 10 groups of data were tested, and the average value was taken to obtain the material cross-sectional porosity; Chemical composition determination: The actual chemical composition of the positive electrode material was determined by ICP-AES. The results showed that the actual chemical composition of each finished product was basically consistent with the designed proportions of each sample in the table.
[0043] Average grain size: calculated according to Scherrer formula, i.e. D=Kλ / (βcosθ). K is a constant, λ is the wavelength of X-rays, (003) or (104) peak is selected, β and θ are the half-height width and diffraction angle of the diffraction peak obtained by Topas software through full spectrum fitting, and K is 0.89.
[0044] Tap density: measured according to the method specified in the national standard GB / T 5162-2006; Powder compaction: Use particle density analyzer: CARVER4350, take samples of 2~3g, use different pressure pressurized molds with radius r=0.65cm, maintain pressure for 1min, measure the sample height after tableting, and get the powder compaction density. The calculation formula is powder compaction density ρ=m / (πr^2 {(h1+h2+h3+h4+h5+h6 ) / 6-d} ); Note: г is the radius of the mold cylinder, d is the height from the upper mold cover to the top of the charging barrel when empty, and h is the height from the upper mold cover to the top of the charging barrel after powder tableting.
[0045] Example 1 This embodiment provides a positive electrode material, the chemical formula of which is: Li 1.15 Ni 0.29 Mn 0.53 W 0.02 La 0.01 O 1.995 S 0.005 . It is prepared by the following preparation method: S1. Hydroxide precursor for synthesizing small-size secondary spherical particles (D 50 = 3.0 μm): S11, preparing a nickel and manganese salt solution with a total molar ratio of 2.5 mol / L, wherein the nickel and manganese sources are nickel sulfate and manganese sulfate, respectively, wherein the molar ratio of nickel to manganese is 35:65; preparing a 10 mol / L sodium hydroxide solution and a 10 wt% ammonia complexing agent solution; S12, fill a 50 L reactor with clean water, set the stirring speed of the reactor to 800 rpm, and the temperature to 55°C; add nitrogen gas, exhaust for 2 hours, and then introduce metal salt solution, precipitant, and complexing agent into the reactor to maintain the pH of the reaction system at 10.0; S13, wait for the particle size to grow to D 50 = After the target particle size reaches 3.0 μm, stop feeding and collect the slurry in the kettle; S14, subjecting the slurry collected in S13 to aging, washing, centrifugation, drying and other treatments to obtain a hydroxide precursor of small-size secondary spherical particles.
[0046] S2. Hydroxide precursor for synthesizing large-size secondary spherical particles (D 50 =10 μm): S21, preparing a nickel and manganese salt solution with a total molar ratio of 2.5 mol / L, wherein the nickel and manganese sources are nickel sulfate and manganese sulfate, respectively, wherein the molar ratio of nickel to manganese is 35:65; preparing a 10 mol / L sodium hydroxide solution and a 10 wt% ammonia complexing agent solution; S22, fill a 50 L reactor with clean water, set the stirring speed of the reactor to 800 rpm, and the temperature to 55°C; add nitrogen gas containing 1.0 vol% oxygen, and after exhausting for 2 hours, introduce a metal salt solution, a precipitant, and a complexing agent into the reactor to maintain the pH of the reaction system at 10.0; S23, wait for the particle size to grow to D 50 = After the target particle size reaches 10.0 μm, stop feeding and collect the slurry in the kettle; S24, subjecting the slurry collected in S23 to aging, washing, centrifugation, drying and other treatments to obtain a hydroxide precursor of large-size secondary spherical particles.
[0047] S3, then, the hydroxide precursor of the above-mentioned small-size secondary spherical particles and the hydroxide precursor of the large-size secondary spherical particles are mixed with lithium carbonate and WO3 additive in a stoichiometric ratio, and sintered once in a box furnace or a roller kiln, with a heating rate of 2°C / min, a sintering temperature of 920°C, and a holding time of 10h, and then naturally cooled to room temperature, crushed, and sieved to obtain a high-density long-cycle positive electrode material; S4. Further mix it with the coating agent Al2O3, control the mass percentage of the coating layer to 0.5%, and perform secondary sintering in a box furnace or a roller kiln, with a heating rate of 2°C / min, a sintering temperature of 600°C, and a holding time of 10h. Then naturally cool to room temperature, crush, and sieve to obtain a coated high-density long-cycle positive electrode material.
[0048] It should be noted that, in this embodiment and other embodiments, step S1 and step S2 are not separated in order and can be performed simultaneously.
[0049] Example 2 This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the chemical formula of the lithium-rich positive electrode material in this embodiment is: Li 1.2 Ni 0.19 Mn 0.58 W 0.02 La 0.01 O 1.995 S 0.005 , which is prepared in the stoichiometric ratio of the chemical formula, l / m=0.62, α / β=1.4, D 50 =7.3μm, Span=1.35, the average grain size is 110nm, and in S12 and S22, the stirring speed is set to 600rpm, the temperature is 50°C, and after the protective gas is introduced for exhaust treatment for 2.5h, the pH of the reaction system is maintained at 9.5. The other preparation steps are the same as those in Example 1 and are not repeated here.
[0050] Example 3
[0051] This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the chemical formula of the lithium-rich positive electrode material in this embodiment is: Li 1.12 Ni 0.34 Mn 0.51 W 0.02 La 0.01 O 1.995 S 0.005 , which is prepared in the stoichiometric ratio of the chemical formula, l / m=0.6, α / β=1.5, D 50 =7.4μm, Span=1.38, the average grain size is 112nm, the stirring speed is set to 1000rpm, the temperature is 60°C, and after the protective gas is introduced for exhaust treatment for 3h, the metal salt solution, the precipitant and the complexing agent are added to maintain the pH of the reaction system at 11.0. The other preparation steps are the same as those in Example 1 and are not repeated here.
[0052] Example 4
[0053] This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the chemical formula of the lithium-rich positive electrode material in this embodiment is: Li 1.15 Ni 0.28 Mn 0.52 Mg 0.02 Al 0.03 O 1.995 S 0.005 , which is prepared in the stoichiometric ratio of the chemical formula, l / m=0.63, α / β=1.61, D 50 =7.5μm, Span=1.42, the average grain size is 118nm, and the parameters of the primary sintering treatment are as follows: the heating rate is 1°C / min, the sintering temperature is 900°C, and the holding time is 8h. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0054] Example 5
[0055] This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the chemical formula of the lithium-rich positive electrode material in this embodiment is: Li 1.15 Ni 0.28 Mn 0.52 Cr 0.04 Mo 0.01 O 1.995 S 0.005 , which is prepared in the stoichiometric ratio of the chemical formula, l / m=0.58, α / β=1.55, D 50=7.4μm, Span=1.44, the average grain size is 103nm, and the parameters of the primary sintering treatment are as follows: the heating rate is 3℃ / min, the sintering temperature is 950℃, and the holding time is 15h. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0056] Example 6
[0057] This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the mass percentage of the coating layer in this embodiment is 2.0%, l / m=0.6, α / β=1.56, D 50 =7.5μm, Span=1.34, the average grain size is 108nm, and the parameters of the secondary sintering treatment are as follows: the heating rate is 1℃ / min, the sintering temperature is 500℃, and the holding time is 8h. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0058] Example 7 This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the material composition of the coating layer of this embodiment is Al2O3 and AlPO4, and the mass percentage is 1.0% and 1.0% respectively, l / m=0.63, α / β=1.48, D 50 =7.4μm, Span=1.41, the average grain size is 108nm, and the parameters of the secondary sintering treatment are as follows: the heating rate is 3℃ / min, the sintering temperature is 700℃, and the holding time is 12h. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0059] Example 8
[0060] This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the material composition of the coating layer of this embodiment is LiAlO2, and the mass percentage is 0.5%, l / m=0.61, α / β=1.52, D 50 =7.43 μm, Span=1.4, the average grain size is 116 nm, the protective gas in step S22 is nitrogen containing 0.5 vol% oxygen, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0061] Comparative Example 1 This comparative example provides a single-size positive electrode material, the chemical formula of which is: Li 1.15 Ni 0.29 Mn 0.53 W 0.02 La 0.0 1O 1.995 S 0.005 The preparation process is as follows: S1. Hydroxide precursor for synthesizing small-size secondary spherical particles (D50 = 3.0 μm): S11, preparing a nickel and manganese salt solution with a total molar ratio of 2.5 mol / L, wherein the nickel and manganese sources are nickel sulfate and manganese sulfate, respectively, wherein the molar ratio of nickel to manganese is 35:65; preparing a 10 mol / L sodium hydroxide solution and a 10 wt% ammonia complexing agent solution; S12, fill a 50 L reactor with clean water, set the stirring speed of the reactor to 800 rpm, and the temperature to 55°C; add nitrogen gas, exhaust for 2 hours, and then introduce metal salt solution, precipitant, and complexing agent into the reactor to maintain the pH of the reaction system at 10.0; S13, wait for the particle size to grow to D 50 = After the target particle size reaches 3.0 μm, stop feeding and collect the slurry in the kettle; S14, subjecting the slurry collected in S13 to aging, washing, centrifugation, drying and other treatments to obtain a hydroxide precursor of small-size secondary spherical particles.
[0062] S2, then, the hydroxide precursor of the above-mentioned small-size secondary spherical particles is mixed with lithium carbonate and WO3 additive in a stoichiometric ratio, and sintered in a box furnace or a roller kiln, with a heating rate of 2°C / min, a sintering temperature of 920°C, and a holding time of 10h, and then naturally cooled to room temperature, crushed, and sieved to obtain a positive electrode material; S3. Further mix it with the coating agent Al2O3, control the mass percentage of the coating layer to 0.5%, and perform secondary sintering in a box furnace or a roller kiln, with a heating rate of 2°C / min, a sintering temperature of 600°C, and a holding time of 10h. Then naturally cool it to room temperature, crush it, and sieve it to obtain the positive electrode material.
[0063] Comparative Example 2 This comparative example provides a single-size positive electrode material, the chemical formula of which is: Li 1.15 Ni 0.29 Mn 0.53 W 0.02 La 0.0 1O 1.995 S 0.005 The preparation process is as follows: S1. Hydroxide precursor for synthesis of large-size secondary spherical particles (D 50 =10 μm): S11, preparing a nickel and manganese salt solution with a total molar ratio of 2.5 mol / L, wherein the nickel and manganese sources are nickel sulfate and manganese sulfate, respectively, wherein the molar ratio of nickel to manganese is 35:65; preparing a 10 mol / L sodium hydroxide solution and a 10 wt% ammonia complexing agent solution; S12, fill a 50 L reactor with clean water, set the stirring speed of the reactor to 800 rpm, and the temperature to 55°C; add nitrogen gas containing 1.0 vol% oxygen, and after exhausting for 2 hours, introduce a metal salt solution, a precipitant, and a complexing agent into the reactor to maintain the pH of the reaction system at 10.0; S13, wait for the particle size to grow to D 50 = After the target particle size reaches 10.0 μm, stop feeding and collect the slurry in the kettle; S14, subjecting the slurry collected in S23 to aging, washing, centrifugation, drying and other treatments to obtain a hydroxide precursor of large-size secondary spherical particles.
[0064] S2, then, the hydroxide precursor of the large-size secondary spherical particles is mixed with lithium carbonate and WO3 in a stoichiometric ratio, and sintered in a box furnace or a roller kiln, with a heating rate of 2°C / min, a sintering temperature of 920°C, and a holding time of 10h, and then naturally cooled to room temperature, crushed, and sieved to obtain a positive electrode material; S3. Further mix it with the coating agent Al2O3, control the mass percentage of the coating layer to 0.5%, and perform secondary sintering in a box furnace or a roller kiln, with a heating rate of 2°C / min, a sintering temperature of 600°C, and a holding time of 10h. Then naturally cool to room temperature, crush, and sieve to obtain a coated positive electrode material.
[0065] Comparative Example 3 This comparative example provides a positive electrode material, which is different from Example 1 only in that, in this comparative example, l / m=1.1, α / β=0.85, D 50 =7.5μm, Span=1.4, the average grain size is 145nm, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0066] Comparative Example 4 This comparative example provides a positive electrode material, which is different from Example 1 only in that, in this comparative example, l / m=0.7, α / β=1.4, D 50 =8.7μm, Span=1.55, the average grain size is 122nm, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0067] Comparative Example 5 This comparative example provides a positive electrode material, which is different from Example 1 only in that, in this comparative example, l / m=0.66, α / β=1.43, D 50 =4.6μm, Span=1.32, the average grain size is 108nm, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0068] Comparative Example 6 This comparative example provides a positive electrode material, which is different from Example 1 only in that, in this comparative example, l / m=0.63, α / β=1.38, D 50 =6.5μm, Span=1.62, the average grain size is 116nm, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0069] Comparative Example 7 This comparative example provides a positive electrode material, which is different from Example 1 only in that, in this comparative example, l / m=0.60, α / β=1.43, D 50 =8.3μm, Span=1.13, the average grain size is 109nm, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0070] Comparative Example 8 This comparative example provides a positive electrode material, which is different from Example 1 only in that, in this comparative example, l / m=0.4, α / β=2.3, D 50 =7.5μm, Span=1.43, the average grain size is 76nm, and the other preparation steps are the same as those in Example 1 and will not be repeated here.
[0071] The inventors summarized the synthesis parameters and physicochemical parameters of Examples 1-8 and Comparative Examples 1-8, and the results are shown in Table 1: Table 1 Synthesis parameters and physicochemical parameters of Examples 1-8 and Comparative Examples 1-8
[0072] Furthermore, the inventors conducted performance tests on the positive electrode materials obtained in Examples 1-8 and Comparative Examples 1-8, and the test results are shown in Table 2: Table 2: Electrical performance results of positive electrode materials obtained in Examples 1-8 and Comparative Examples 1-8
[0073] In Table 2, M represents small-size secondary spherical particles, and L represents large-size secondary spherical particles; In addition, the inventors further observed the positive electrode material described in Example 1, and the results were as follows: Figure 1 As shown, from Figure 1 It can be seen that in the positive electrode material prepared in Example 1, the size of the primary spherical particles constituting the large-diameter secondary spherical particles is significantly smaller than the size of the primary spherical particles constituting the small-diameter secondary spherical particles.
[0074] Furthermore, the inventors summarized the particle size distribution of the positive electrode materials obtained in Example 1, Comparative Example 1 and Comparative Example 2, and the results are as follows: Figure 2 As shown, from Figure 2It can be seen that the particle size of the positive electrode material prepared by the comparative example is a single particle size distribution, while the particle size of the positive electrode material prepared by Example 1 is a double particle size distribution, and the double peak position basically coincides with the single peak position in the comparative example, indicating that the positive electrode material prepared by the preparation method of the present invention is indeed composed of large and small particle samples of two single particle size distributions, and this distribution can further provide a higher compaction density.
[0075] Furthermore, the inventors conducted statistical analysis on the powder compaction densities of the positive electrode materials obtained in Example 1, Comparative Example 1, and Comparative Example 2 under different pressures. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the compaction density of the small particle single size distribution sample is lower, and the compaction density of the large particle single size distribution sample is improved, but the double-peak dual-size distribution sample can achieve the highest compaction density.
[0076] The inventors further performed performance tests by assembling liquid button half-cells: the positive electrode materials obtained in Examples 1-8 and Comparative Examples 1-8 were assembled into liquid button half-cells, and the assembly method was as follows: the obtained positive electrode material, conductive agent Super-P, and adhesive PVDF were added to NMP solvent in a ratio of 94:3:3 and mixed evenly to obtain a slurry, and the obtained slurry was sequentially subjected to coating-drying-punching-rolling to obtain a positive electrode sheet, and the button battery stainless steel shell, positive electrode sheet, PP diaphragm, and lithium sheet were stacked in sequence, and a certain amount of electrolyte was added and then packaged and kept stationary to obtain a liquid button half-cell.
[0077] Liquid button half-cells are tested as follows: 1. 0.2C discharge capacity Test method: After the assembled battery has been idle for 5 hours, it is charged to 4.55V at a constant current of 0.2C, then charged to a cut-off current of 0.05C at a constant voltage of 4.55V, and then discharged to 2.5V at a constant current of 0.2C after being idle for 5 minutes. The resulting discharge capacity is the 0.2C discharge capacity.
[0078] 2. First Coulombic efficiency Test method: After the assembled battery has been idle for 5 hours, it is charged to 4.55V at a constant current of 0.2C, then charged to a cut-off current of 0.05C at a constant voltage of 4.55V, and then discharged to 2.5V at a constant current of 0.2C after being idle for 5 minutes; the obtained discharge capacity / charge capacity is the first coulombic efficiency.
[0079] 3. Capacity retention rate after 150 cycles at 1.0C Test method: After the battery has tested the first cycle discharge capacity, charge it at 1.0C constant current to 4.55V, then charge it at 4.55V constant voltage to a cut-off current of 0.05C, and then discharge it at 1.0C constant current to 2.5V after 5 minutes of rest. Repeat this 150 times, i.e., charge and discharge it at 1.0C rate for 150 cycles. The discharge capacity of the 150th cycle / the discharge capacity of the first cycle is the capacity retention rate of 150 cycles at 1.0C.
[0080] Application Examples The prepared positive electrode was subjected to battery testing. The capacity, specific energy and cycle performance of the positive electrode endowed by the matrix were verified through battery testing. For lithium button batteries with a voltage of 2.5-4.55V and a nominal capacity of 250mAhg-1, the first cycle was charged and discharged at 0.1C, then charged and discharged at 2.0C for one cycle, and then cycled 150 times at 1.0 / 1.0C.
[0081] The test results are shown in Table 3: Table 3: Performance test results of liquid button half-cells assembled from positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-8
[0082] Furthermore, the inventors tested the cycle performance of the liquid button half-cells assembled from the positive electrode materials obtained in Example 1, Comparative Example 1, and Comparative Example 2. The test results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the double-peaked dual-particle size distribution sample has better performance than the single-particle size distribution sample due to the better gradation between particles, and the battery made of its positive electrode material has higher cycle stability.
[0083] It can be seen from the data results of Comparative Examples 1 and 2 that the capacity of a single small-particle secondary spherical lithium-rich positive electrode or a single large-particle secondary spherical lithium-rich positive electrode that meets the requirements of L and M is acceptable, but the compaction density is too low, and the cycle stability is poorer than that of the particle size dual-distribution lithium-rich positive electrode described in the present invention. Therefore, the energy density and stability that can be provided by the positive electrode material of a single particle size are low and cannot meet the requirements of industrialization; it can be seen from the data results of Comparative Example 3 that when the size of the primary particles constituting L is too large and does not meet the conditions described in the present invention, its porosity decreases significantly, the capacity of the system decreases significantly, the power performance is insufficient, and the volume energy density is lower than that of a single particle size product. In addition, due to the large size of the primary particles constituting L, its kinetic performance is poor, and the 1C / 1C cycle performance is also significantly deteriorated; it can be seen from the data results of Comparative Examples 4 and 5 that when the L particle size is too large, the capacity of the system will be limited because the lithium ion transmission distance in L is too long; when the L particle size is too small, the compaction density of the system cannot meet the requirements and cannot provide an ideal volume energy density. From the data results of Comparative Examples 4 and 5, it can be seen that when the particle size of M is too small, the cycle stability is reduced, because at this time M can be deeply delithiated, and the structural decay rate is accelerated. When the particle size of M is too large, the system compaction density is reduced, because at this time it is difficult for M to completely fill the gaps left by L, resulting in L being unable to be densely packed. From Comparative Example 8, it can be seen that when the size of the primary particles constituting L is too small, due to the increase in the porosity of L and the decrease in the average grain size, the system compaction density is significantly reduced, the system specific surface area is increased, the interface side reaction is aggravated, and the cycle stability is significantly reduced.
[0084] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A positive electrode material, characterized in that: The particle size distribution curve of the positive electrode material is a bimodal distribution. The positive electrode material is composed of large-diameter secondary spherical particles and small-diameter secondary spherical particles, and the large-diameter secondary spherical particles are composed of small-diameter primary spherical particles, and the small-diameter secondary spherical particles are composed of large-diameter primary spherical particles. The D50 of the large-diameter secondary spherical particles is 8.0-12.0 μm, and the D50 of the small-diameter secondary spherical particles is 2.0-4.0 μm, wherein the maximum diameter of the small-diameter secondary spherical particles does not exceed 5 μm, and the minimum diameter of the large-diameter secondary spherical particles is not less than 5 μm; the average particle size of the small-diameter primary spherical particles and the large-diameter primary spherical particles meets the following requirements: 0.5≤l / m≤0.75, Wherein l is the average particle size of the small-diameter primary spherical particles, and m is the average particle size of the large-diameter primary spherical particles.
2. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Li 1+ x Ni t Mn u M 1-x-t-u O 2-z S z , wherein 0.1≤x≤0.2, 0.1≤t≤0.4, 0.5≤u≤0.7, 0.002≤z≤0.02, 0.95≤x+t+u<1.0, and M is selected from one or more of Nb, Cr, Ta, P, Mg, Ti, Mo, W, Sn, Sr, Al, Y, La, Zr, Ce, Si, Ba, and B.
3. The positive electrode material according to claim 1, characterized in that It also includes a coating layer, and the material of the coating layer is selected from one or more of Al2O3, LiAlO2, Li3PO4, and AlPO4, and the mass proportion of the coating layer in the positive electrode material is 0.2-2.0wt%.
4. The positive electrode material according to claim 1, characterized in that The D50 of the positive electrode material is 5.0-8.0 μm; And / or, the average grain size of the positive electrode material is 80-130 nm; And / or, the Span value of the positive electrode material is 1.2-1.6, wherein Span=(D 90 -D 10 ) / D 50 ; And / or, the specific surface area of the positive electrode material is 0.7-3.0m 2 / g; And / or, the cathode material has a powder compaction density of ≥3.05 g / cm at a pressure of 3.5 T. 3 .
5. The positive electrode material according to claim 1, characterized in that In the particle size distribution curve of the positive electrode material, the relative height of the left peak and the relative height of the right peak satisfy: 0.3≤I A :I B ≤0.6, where I A is the relative height of the left peak, I B is the relative height of the right peak.
6. The positive electrode material according to claim 1, characterized in that The cross-sectional porosity of the large-diameter secondary spherical particles and the cross-sectional porosity of the small-diameter secondary spherical particles satisfy: 1.2≤α / β≤1.8, wherein α is the cross-sectional porosity of the large-diameter secondary spherical particles, and β is the cross-sectional porosity of the small-diameter secondary spherical particles.
7. A method for preparing a positive electrode material according to any one of claims 1 to 6, characterized in that: The preparation method specifically comprises the following steps: S1. synthesizing a hydroxide precursor of small-size secondary spherical particles and a hydroxide precursor of large-size secondary spherical particles respectively; S2, mixing the lithium source, additives, the hydroxide precursor of the small-size secondary spherical particles and the hydroxide precursor of the large-size secondary spherical particles obtained in step S1, sintering them once, cooling them, and then crushing and sieving them to obtain the positive electrode material.
8. The preparation method according to claim 7, characterized in that: In step S1, the specific steps of synthesizing the hydroxide precursor of small-size secondary spherical particles are as follows: A1. Set the stirring speed to 600-1000 rpm and the temperature to 50-60°C. After passing the protective gas for exhaust treatment for 2-3 hours, add the metal salt solution, precipitant and complexing agent to maintain the pH of the reaction system at 9.5-11.0; A2, wait until the particle size grows to D 50 In the range of 2.0-4.0 μm, stop feeding and collect the slurry; A3, the slurry collected in step A2 is aged, washed, centrifuged, and dried in sequence to obtain a hydroxide precursor of small-size secondary spherical particles; The specific steps for synthesizing the hydroxide precursor of large-size secondary spherical particles are as follows: B1. Set the stirring speed to 600-1000 rpm and the temperature to 50-60°C. After introducing protective gas for exhaust treatment for 2-3 hours, add metal salt solution, precipitant and complexing agent to maintain the pH of the reaction system at 9.5-11.0; B2, wait until the particle size grows to D 50 In the range of 8.0-12.0 μm, stop feeding and collect the slurry; B3. The slurry collected in step B2 is subjected to aging, washing, centrifugation and drying treatments in sequence to obtain a hydroxide precursor of large-size secondary spherical particles.
9. The preparation method according to claim 8, characterized in that: In the step A1 and the step B1, the total molar concentration of the metal salt solution is 2-3 mol / L, and the solute is nickel sulfate and manganese sulfate, wherein the molar ratio of nickel to manganese is the same as the ratio of the small-size secondary spherical particles, the precipitant is a sodium hydroxide solution with a concentration of 8-12 mol / L, and the complexing agent is an 8-12 wt% ammonia solution; And / or, the protective gas in step A1 is nitrogen, and the protective gas in step B1 is nitrogen containing 0.5-5.0 vol% oxygen.
10. The preparation method according to claim 8, characterized in that: The method also includes step S3, mixing the positive electrode material and the coating agent uniformly, performing secondary sintering, cooling, crushing and sieving in sequence to obtain a positive electrode material containing a coating layer, wherein the coating agent is selected from one or more of Al2O3, LiAlO2, Li3PO4 and AlPO4.
11. The preparation method according to claim 10, characterized in that: The parameters of the primary sintering are as follows: heating rate is 1-3°C / min, sintering temperature is 900-950°C, and holding time is 8-15h; And / or, the parameters of the secondary sintering are as follows: heating rate is 1-3°C / min, sintering temperature is 500-700°C, and holding time is 8-12h.
12. Use of the positive electrode material according to any one of claims 1 to 6 in a lithium ion battery.
Citation Information
Patent Citations
Positive electrode material, positive electrode comprising same, and electrochemical device comprising positive electrode material
CN110416511A
Agglomeration-like multi-element positive electrode material, preparation method and application thereof, and lithium ion battery
CN116111081A
Positive electrode active material and lithium secondary battery including same
CN117954588A
Cobalt-free polycrystalline layered material, composite material, positive plate and battery
CN119153680A
Positive electrode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
US20220059836A1
Cited By
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN121247755A
Positive electrode material, and preparation method therefor and use thereof
WO2026149444A1